Antimicrobial, Antioxidant, Anti-Inflammatory and Cytotoxic Activities of Garcinia Eugenifolia and Calophyllum Enervosum - Bakhtiar, M. Taher; Muhammad Sum , Idris; Dayar, Arbain (Razi Institute for Drug Research of IUMS, 2007)
Chemical investigation of Garcinia eugenifolia and Calophyllum enervosum yielded six compounds. One of these was found to be a novel compound identified as enervosanone. Five known compounds cambogin, epicatechin, osajaxanthone, rubraxanthone and isocowanol, were also isolated. These compounds were tested for their bioactivity as antimicrobial, antioxidant and cytotoxicagents. Antimicrobial assay was performed using disc diffusion method. The antioxidative activity was evaluated using 2,2-diphenyl-1-picrylhydrazyl (DPPH) method by electron spin resonance. The cytotoxicity was measured by the MTT assay against MCF7 cell line. Enervosanone and rubraxanthone were active against Bacillus subtilis, Escherichia coli, Pseudomonas aeruginosa and Staphylococcus aureus with MIC value of 26.82, 26.82, 26.82, 26.82 and 60.97, 30.48, 60.97, 60.97 mM, respectively. Rubraxanthone and epicatechin exhibited antioxidant activities with IC50 of 0.89 mM and 2.6 mM, respectively. The cytotoxicity assay on MCF7 cell line showed that enervosanone was found to be active in inhibiting cell proliferation of MCF7 with IC50 of 1.07 mM.